A Psychological Reading of The Problem of the Black in John Steinbeck’s Of (Mice and Men) (Journal of the College of Languages (JCL), 2020)
The present paper applies Fanon Psychological reading of the problem of the Black introduced in his book Black Skin White Mask to Crooks, The black Character in John Steinbeck’s Of Mice and Men. The analysis of this character infers three essential points regarding the artistic achievement of the author. First, he uses a fictional character that offers a psychological interpretation of the black problem of alienation and loneliness in a way that does not disgrace the black. Second, he applies Fanon’s way of showing the various attitudes that the black adopts in contact with the white society. Third, he affirms that the black inferiority complex comes as a result of double process: economic and the internalization of this complex.